Reciprocal Mentorship as Trans-Systemic Knowledge: A Story of an Indigenous Student and a Non-Indigenous Academic Supervisor Navigating Graduate Research in a Canadian University - Bishop, Kathy; Webster, Christine (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2021)
Reciprocal mentorship is how Indigenous students and non-Indigenous supervisors can supportively navigate their way through graduate research in higher education. Reciprocal mentorship as trans-systemic knowledge values both Indigenous and Eurocentric worldviews, whereby the student has the expertise from Indigenous community and the academic supervisor has the expertise in the academic world. Through sharing stories of their research journey within a Canadian University, Webster and Bishop offer key insights around engaging in reciprocal mentorship, navigating the two-worlds, finding a common language, and having shared values. As a result, Indigenous and non-Indigenous students and supervisors may see themselves within the stories and seek reciprocal mentorship to be successful in the academic research and educational journey and make an impact in their university and beyond.